Sejarah dan Perkembangan Pencak Silat Panglipur Mekar Buana di Cikole Lembang tahun 2011-2020 - M Ilham Nurjaman (Priangan: Journal of Islamic Sundanese Culture, 2025)
Pencak Silat Panglipur is a martial arts school in Bandung which was founded by Abah Aleh in 1909. Panglipur continues to grow in Indonesia and even abroad. One branch that is growing is Panglipur Mekar Buana. This article aims to find out the history and development of the Panglipur Mekar Buana pencak silat from 2011 to 2020. The method used is historical research methods starting from heuristics, verification, interpretation and historiography. Pencak Silat Panglipur Mekar Buana was founded by Asep Dedi Suherman on 2 November 2011 which is a division of Panglipur Langlangbuana. Asep studied silat from a young age from grade 3 in elementary school until he was 18 years old. Then Aki Tarmedi gave a mandate to spread Panglipur.